(untitled) (Fiep Bulletin - online, 2013)
This study aims to identify the profile of aggression in school children in school, the municipality of Santa Cruz do Sul, Rio Grande do Sul were research subjects, students of 5th to 8th year, while 63 are male and 77 females. The methodological approach was exploratory and descriptive data collection questionnaire was used. The results show that almost half of the boys of the research have been assaulted in some way. It can be said, too, that the place where it happens most of the assaults is at recess, or during rest breaks between classes. Among various types of aggression, boys suffer more with physical and verbal aggression, girls with verbal. For most students, teachers try to prevent students agridam, and speak because they have assaulted someone. Most students parents spoke for assaulting someone at school. When asked if their parents know they are assaulted, most reports do not comment on the attacks at home. Still, in this study, it can be concluded within a profile of aggression, the aggressor in most cases is a student or several male students and one female student.